2014
DOI: 10.1074/jbc.m114.557447
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stem Cells Suppress Host Rejection

Abstract: Background: Umbilical cord mesenchymal stem cells (UMSCs) have unique immunosuppressive properties. Results: UMSCs express a rich glycocalyx, which confers their ability to modulate both macrophages and T-regulatory cells and to lead to inflammatory cell death. Conclusion: UMSCs actively modulate inflammatory cells by suppressing the immune response and evading rejection. Significance: Engineering cells to express this rich glycocalyx could increase transplantation success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 47 publications
1
86
0
1
Order By: Relevance
“…However, we have recently shown that UMSCs have unique immunosuppressive properties that can prevent xenograft rejection, making these cells extremely attractive for cell therapy. 27 Our study demonstrated that UMSCs actively regulate immune cells, inhibiting M1 polarization and promoting M2 polarization in an extracellular matrix-dependent manner.…”
Section: Immunosuppressive Properties Of Mesenchymal Stem Cellsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, we have recently shown that UMSCs have unique immunosuppressive properties that can prevent xenograft rejection, making these cells extremely attractive for cell therapy. 27 Our study demonstrated that UMSCs actively regulate immune cells, inhibiting M1 polarization and promoting M2 polarization in an extracellular matrix-dependent manner.…”
Section: Immunosuppressive Properties Of Mesenchymal Stem Cellsmentioning
confidence: 62%
“…26 In the case of T cells, MSCs primarily promote the activation of T regulatory cells. 27,28 In the case of B cells, MSCs inhibit B-cell proliferation, plasma-cell differentiation, and antibody production, all in a T-cell-dependent manner. 29 To date, MSCs have been shown to regulate the innate and adaptive immune responses primarily in a cytokine-dependent manner through the secretion of transforming growth factor-beta ( TGFβ ), interferon gamma ( IFNγ ), prostaglandin E2 ( PGE2 ), interleukin ( IL )-10 and tumor necrosis factor-alpha ( TNFα ).…”
Section: Immunosuppressive Properties Of Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting to know that Coulson-Thomas et al (46) have recently demonstrated that MSCs from umbilical cord express a rich glycocalyx composed of the chondroitin sulfate proteoglycan versican bound to the SHAP-HA complex and could modulate inflammatory cells to reduce the immune response and suppress rejection. This mechanism might be operative in part for the settlement of MSCs transplanted in the damaged muscle and for that of MSCs injected in the intact muscle after activation by the C2C12 lysate, which we observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is not consensual if allogeneic delivery of MSCs would lead to immune rejection. Actually, many findings with somatic stem cells showed that they possess immunossupressive action, not being rejected by the host organism [99][100][101][102] . If lack of immune rejection becomes confirmed for allogeneic somatic stem cell transplants, this would certainly represent the preferred option, making it possible that cultured cells are readily available for the patients.…”
Section: Stem Cell Types and Clinical Applications: An Everemerging Smentioning
confidence: 99%